Hypoxic condition enhances chondrogenesis in synovium-derived mesenchymal stem cells - Hyun Cheol Bae; Hee Jung Park; Sun Young Wang; Ha Ru Yang; Myung Chul Lee; Hyuk-Soo Han (Biomaterials Research, 2018)
Abstract Background The chondrogenic differentiation of mesenchymal stem cells (MSCs) is regulated by many factors, including oxygen tensions, growth factors, and cytokines. Evidences have suggested that low oxygen tension seems to be an important regulatory factor in the proliferation and chondrogenic differentiation in various MSCs. Recent studies report that synovium-derived mesenchymal stem cells (SDSCs) are a potential source of stem cells for the repair of articular cartilage defects. But, the effect of low oxygen tension on the proliferation and chondrogenic differentiation in SDSCs has not characterized. In this study, we investigated the effects of hypoxia on proliferation and chondrogenesis in SDSCs. Method SDSCs were isolated from patients with osteoarthritis at total knee replacement. To determine the effect of oxygen tension on proliferation and colony-forming characteristics of SDSCs, A colony-forming unit (CFU) assay and cell counting-based proliferation assay were performed under normoxic (21% oxygen) or hypoxic (5% oxygen). For in vitro chondrogenic differentiation, SDSCs were concentrated to form pellets and subjected to conditions appropriate for chondrogenic differentiation under normoxia and hypoxia, followed by the analysis for the expression of genes and proteins of chondrogenesis. qRT-PCR, histological assay, and glycosoaminoglycan assays were determined to assess chondrogenesis. Results Low oxygen condition significantly increased proliferation and colony-forming characteristics of SDSCs compared to that of SDSCs under normoxic culture. Similar pellet size and weight were found for chondrogensis period under hypoxia and normoxia condition. The mRNA expression of types II collagen, aggrecan, and the transcription factor SOX9 was increased under hypoxia condition. Histological sections stained with Safranin-O demonstrated that hypoxic conditions had increased proteoglycan synthesis. Immunohistochemistry for types II collagen demonstrated that hypoxic culture of SDSCs increased type II collagen expression. In addition, GAG deposition was significantly higher in hypoxia compared with normoxia at 21 days of differentiation. Conclusion These findings show that hypoxia condition has an important role in regulating the synthesis ECM matrix by SDSCs as they undergo chondrogenesis. This has important implications for cartilage tissue engineering applications of SDSCs.